1. (2x-3)(3x+4)=(3x+4)(x-5)

6x² - x - 12 = 3x² - 11x - 20 {used foil method on both sides}

3x² + 10x + 8 = 0 {subtracted 3x², added 11x, and added 20 to both sides}

(3x + 4)(x + 2) = 0 {factored into two binomials}

3x + 4 = 0 or x + 2 = 0 {set each factor equal to 0}

3x = -4 or x = -2 {subtracted 4 and subtracted 2, respectively}

**x = -4/3 or x = -2** {divided left equation by 3}

2. (x^2-4)(4x^2 - 4x - 15) = 0

(x + 2)(x - 2)(2x + 3)(2x - 5) = 0 {factored everything}

x + 2 = 0 or x - 2 = 0 or 2x + 3 = 0 or 2x - 5 = 0 {set each factor equal to 0}

x = -2 or x = 2 or 2x = - 3 or 2x = 5 {solving each equation for x}

**x = -2 or x = 2 or x = -3/2 or x = 5/2
**

*- Algebra House*
**
**